Field notes contributed by Diane C. Porter, December 2, 1996 - Porter, Diane C.et al (1996)
List of birds and locations contributed by Diane C. Porter. The field notes include detailed descriptions of several species. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed